2021
DOI: 10.1093/emph/eoab004
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering LINE-1’s role in cancer: does LINE-1 function as a reporter detecting early cancer-associated epigenetic signatures?

Abstract: Long Interspersed Nuclear Element-1 (LINE-1 or L1) is the only autonomously active retrotransposon in humans. While L1 has been implicated in several pathologies and the aging process, I present a model which challenges an understanding of L1 as predominantly antagonistic to human health. I hypothesize that L1 serves as a reporter in an early cancer alert system: a tripwire strung throughout the genome poised to trigger p53 and a type I interferon (IFN-1) response when the epigenetic landscape portends cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…A possible explanation for the presence of detectable levels of anti-ORF1p antibodies in healthy subjects is the presence of occult disease, or alternatively, that these antibodies remain as a memory of adaptive immune response to past events associated with the derepression of L1 (e.g., initiated carcinogenic processes intercepted by anticancer defense mechanisms). In fact, it has been demonstrated that L1 derepression can precede cancer development (Kelsey et al, 2021). According to this model, low levels of anti-L1 antibodies in healthy individuals may be "remnants" of a past success of antitumor immunity, whereas the strong accumulation of anti-L1 antibody titers in the blood likely signals persistent activation of associated memory B-cells by the presence of L1-expressing cells and may reflect an inability of the immune system to effectively eradicate these cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the presence of detectable levels of anti-ORF1p antibodies in healthy subjects is the presence of occult disease, or alternatively, that these antibodies remain as a memory of adaptive immune response to past events associated with the derepression of L1 (e.g., initiated carcinogenic processes intercepted by anticancer defense mechanisms). In fact, it has been demonstrated that L1 derepression can precede cancer development (Kelsey et al, 2021). According to this model, low levels of anti-L1 antibodies in healthy individuals may be "remnants" of a past success of antitumor immunity, whereas the strong accumulation of anti-L1 antibody titers in the blood likely signals persistent activation of associated memory B-cells by the presence of L1-expressing cells and may reflect an inability of the immune system to effectively eradicate these cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Another valuable property of anti-L1 IgG antibodies with respect to their diagnostic potential is that their elevation is frequently observed in patients with early (1-2) stages of cancer. This is likely explained by the fact that L1 expression frequently occurs at early stages of malignant transformation and either stays high during tumor progression (Zhang et al, 2020 and Grundy et al, 2022; Kelsey et al, 2021) or, in some instances, may decrease (Guler et al, 2017). This feature distinguishes anti-L1 antibody response from that of other autoantibodies considered as potential cancer biomarkers, which are limited in their value for early cancer detection since they are more commonly associated with advanced stages of disease (e.g., to p53, heat shock proteins, etc.…”
Section: Discussionmentioning
confidence: 99%
“…While TEs are commonly recognized for their tumor-promoting functions, recent studies have suggested that RTEs, including active LINE-1 and ERVs, have been evolutionarily selected for their tumor-suppressing function through their ability to induce viral mimicry and/or p53 activation (50). Accordingly, TE transcription is commonly suppressed along tumor progression, for example from low-grade to high grade MDS, then a full-blown AML (43), where a low repeat/gene expression ratio correlates with a poor outcome (51).…”
Section: Discussionmentioning
confidence: 99%
“…TEs are commonly recognized as tumor promoters (Jang et al, 2019; Grundy et al, 2021). However, by their capacity to induce DNA damage and activate cell cycle arrest, senescence and inflammatory responses, these sequences may also be viewed as tumor suppressors (Grundy et al, 2021; Kelsey, 2021). TE expression, and notably that of active full-length L1 capable of retrotranspositoin (L1Hs) is decreased in AML and MDS samples as compared to healthy CD34 + progenitor cells (Kazachenka et al, 2019; Gu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%